Implementation of Fuzzy AHP in Prioritizing Hotel Selection for Various Activities - Osvaldo Fernandy Wijaya; Iswavigra, Dwi Utari Iswavigra; Yunita Rahmasari (SEULANGA SYSTEM PUBLISHER, 2024)
The hotel sector plays a pivotal role in tourism, serving as a crucial venue for businesspeople, tourists, and other guests, significantly boosting regional and national economies. Facing increasing competition due to the rise in attractive tourist destinations and business travel for specific agendas such as meetings and seminars, the hotel industry must optimize its selection process. This study aims to aid in hotel selection based on weighted criteria for various activities by implementing the Fuzzy Analytical Hierarchy Process (Fuzzy AHP). AHP, widely used for multi-criteria decision-making, and Fuzzy Logic, chosen for its effectiveness in handling uncertainty and ambiguity, form the methodological foundation. The study utilized criteria such as price, quality, security, and location, with alternatives including traveling, meetings, and seminars. Data from 30 anonymous respondents were processed using Microsoft Excel for Fuzzy AHP computations. Results indicated that for meetings, hotel selection prioritizes quality and security, while for seminars, price and location are more important. In traveling, the emphasis is evenly distributed but generally low across all criteria, with location being least significant. This research underscores the potential of Fuzzy AHP in improving decision-making accuracy in hotel selection based on varying activity preferences.